Can Marsh Harrier Circus aeruginosus prey on Great Bustard Otis tarda?. Issue 2 (3rd April 2018) - Mirzanejad, Hashem; Gholami, Jafar; Qashqaei, Ali Turk
Abstract: Predator-prey interaction is one of the hottest subjects to study in ecology and many researchers have become interested in this subject. There is little information on feeding habits of birds of prey in the Middle East. In early January 2017, we recorded a Marsh Harrier Circus aeruginosus on a dead Great Bustard Otis tarda in NW Iran. The Great Bustard has not yet been listed in the prey list of the Marsh Harrier. According to literature, the Marsh Harrier occasionally hunts on large birds such as Herring Gull Larus argentatus and geese in Northern Europe. We observed the Marsh Harrier on a dead Great Bustard thinking about whether the former could have killed the latter. Both species are protected by the Department of Environment in Iran, and the Great Bustard is 'Vulnerable' in the IUCN Red List.